Childhood Trauma Is Nominally Associated With Elevated Cortisol Metabolism in Severe Mental Disorder - Aas, Monica; Ueland, Torill; Inova, Amina; Melle, Ingrid; Andreassen, Ole A.; Steen, Nils Eiel (Frontiers in Psychiatry, 2020)
Objective: Individuals exposed to childhood trauma show long-term changes in the major biological stress system, the Hypothalamic-Pituitary-Adrenal (HPA) axis, together with cognitive impairments. Schizophrenia spectrum disorder (SZ) and bipolar disorders (BD) are characterised by higher prevalence of childhood trauma, abnormal HPA axis, and cognitive dysfunction. However, it is yet to be established if childhood adversity is associated with cortisol metabolism in this population, and how this may be associated with cognitive function. Methods: One-hounded-and-fourteen patients with a DSM-IV SZ or BD were included in the study. Diagnoses were assessed using the Structured Clinical Interview for DSM-IV Axis I disorders (SCID-I). Estimated cortisol metabolizing enzyme activity was based on measurements of urinary free cortisol, and metabolites. All patients underwent cognitive assessment and history of childhood trauma was assessed using the Childhood Trauma Questionnaire. Results: Estimated 5α-reductase and 5β-reductase activity was elevated were elevated in patients with a history of childhood trauma experiences, specifically, 5β-reductase and physical abuse (r=0.26, p=0.005). After adjusting for age, sex and diagnosis, a history of physical abuse was still associated with elevated 5β-reductase. Moreover, high 5α-reductase activity, but not 5β-reductase, was negatively correlated with working memory and executive performance (r=-0.24, p=0.01; r=-0.20, p=0.04, respectively), however this was no longer statistically significant after adjusting for age, sex and diagnosis. Cortisol metabolism did not mediate the association between childhood trauma and cognitive function. Conclusions: Our study indicates that physical abuse in childhood is associated with elevated cortisol metabolism (5β-reductase) in adults with a SZ or BD disorder.